1995
DOI: 10.1182/blood.v85.2.541.bloodjournal852541
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the blood group Wright antigens are associated with a mutation at amino acid 658 in human erythrocyte band 3: a site of interaction between band 3 and glycophorin A under certain conditions [see comments]

Abstract: The Wright (Wr) blood group antigens, Wra and Wrb, have been suggested to be determined by alleles of the same gene. The Wrb antigen appears to involve both red blood cell (RBC) band 3 and glycophorin A (GPA). We have examined the cDNA sequences of the band 3 and GPA of one of the two known Wr(a+b-) individuals. We show that this individual is homozygous for the mutation Glu658--<Lys in band 3, but has normal GPA. Putative heterozygotes with Wr(a+b+) RBCs have both Glu and Lys at residue 658 of band 3, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 0 publications
3
21
0
1
Order By: Relevance
“…In this study, we compared the expression of the Wright antigens in Mi.III vs. the non-Mi.III RBCs. The Wr a ⁄ Wr b dimorphism is determined by residue 658 of band 3: Lys-658 yields the Wright a (Wr a ) phenotype, whereas Glu-658 yields Wright b (Wr b ) [16]. Wr b is the predominant phenotype worldwide and in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we compared the expression of the Wright antigens in Mi.III vs. the non-Mi.III RBCs. The Wr a ⁄ Wr b dimorphism is determined by residue 658 of band 3: Lys-658 yields the Wright a (Wr a ) phenotype, whereas Glu-658 yields Wright b (Wr b ) [16]. Wr b is the predominant phenotype worldwide and in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…The altered expression of Wr b on the proband's RBCs is not unexpected because although the Wr b antigen is associated with glutamic acid at Amino Acid 658 of Band 3, its expression requires the presence of Amino Acid Residues 59 to 76 of GPA. 6,7 The amino acid changes associated with ENEP-and ENAV-phenotype RBCs are within this region of GPA and the RBCs have an altered expression of Wr b antigen. 8 Similarly, we have shown that the amino acid change at Residue 62 of GPA on ENEV-RBCs alters expression of Wr b .…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming increasingly clear that different red cell surface proteins may associate together in the normal membrane. There is strong evidence that the two most abundant proteins, band 3 and GPA, are closely associated (Tanner, 1993a,b) and that the Wrb antigen may depend upon this association (Bruce et al, 1994b). The Rh polypeptides associate with the Rh glycoprotein ( Fig.…”
Section: O N C L U D I N G Remarksmentioning
confidence: 98%
“…In this case, amino acid 658 on the fourth extracellular loop is involved. In Wr"-negative cells residue 658 is glutamic acid whereas in Wrapositive cells it is lysine (Table 2, Bruce et al, 1994b).…”
mentioning
confidence: 99%